Pseudologia Fantastica in the Emergency Department: A Case Report and Review of the Literature. (10th May 2017) - Thom, Robyn; Teslyar, Polina; Friedman, Rohn
Abstract : Psychiatrists commonly encounter deception in the emergency department. This article presents the case of a patient who presents to the emergency department with an unusual and elaborate web of deceptions along multiple themes including feigning medical illness, multiple losses, and grandiose academic and athletic achievements. We review the clinical characteristics of pseudologia fantastica and discuss how this patient's constellation of malingering, factitious disorder, and personality disorder suggests this diagnosis.